Pemanfaatan Teknologi Informasi dalam Membantu Pembelajaran Sosiologi di Masa COVID-19 di SMA Negeri 5 Kupang - Maria Sari Narut (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2023)
The aim of this research was to know how the utilize information technology as a learning medium. and to find out what obstacles teachers and students face when participating in learning during COVID-19. This research used qualitative methods. The subjects in this research were sociology teachers and students. This research data was collected through observation, in-depth interviews, and documentation. The data analysis techniques used data collection, data reduction, data presentation, and drawing conclusions. The results of this study show that the learning process during the COVID-19 pandemic at SMA Negeri 5 Kupang continues to run well because sociology teachers have made maximum use of technology. Currently, there is a lot of technological information that can be used as learning media that can help teachers and students during learning, such as WhatsApp, Zoom and Classroom which are used in learning. However, there are still several obstacles in the learning process, such as economic problems which make it difficult for students to buy cell phones and internet quotas, poor networks, supervision, and lack of understanding from students.